Urethral catheterization: do nurses have adequate exposure? - Selvaraj, Nivash; Rajendran, Sudha Dhiyanesh; Farman, Matheen Jaffer (International Surgery Journal, 2021)
Background: Urethral catheterization is a vital basic skill which not learnt properly will lead to numerous complications. The aim of the study is to assess the knowledge and practice of urethral catheterization procedure among the nursing students. Methods: This study was conducted by a questionnaire to all the nurses in our hospital. It includes precautionary methods, knowledge of urethral catheterization procedure and the necessity for the demonstration of the procedure to the nurses. Results: A total of 120 nurses were included in the study. During training program, all were able to define and observed urethral catheterization. Overall, 19% did not perform the procedure as undergraduates and only14% passed >10 urethral catheterization. On assessing the steps, 61% described the steps involved in catheterization and 87% listed the possible complications of catheterization. Meanwhile, 93% revealed the need for practical demonstration of procedure during their training phase. Conclusions: With regards to urethral catheterization, poor practical experience was observed in nurses. An attempt should be formulated to enhance the supervised urethral catherization training programme conducted for nurses, in order to deliver preventable complications.